Foam concrete beam with circular hollow section - Muhammad Adib Aiman, Roseli (2014)
A normal concrete with a density range in between 2400 kg/m 3 to 2500 kg/rn3 proved to be heavy to hoisted to a height in turn the needs of heavy lifting machinery are required especially in precast concrete structures construction. Foam concrete can be categorized as lightweight concrete as the density is less than 2000 kg/rn 3 around 1600 kg/M3 to 1800 kg/rn 3 where this could reduce overall weight of the structures. Another idea of reducing the weight is by forming hollows along the structures such as precast hollow-core slab provided the hollow is formed not at critical location such as where the compression is the highest. Many parameters may influence the overall hollow column response such as the shape of the section, the amount of the longitudinal and transverse reinforcement, the cross section thickness, the axial load ratio and finally the material strength of concrete and reinforcement. This study program focus on the types of failure of circular hollow cross sections beam and plot the crack pattern of the beam under bending. Four simply supported beam with difference circular hollow section and one rectangular solid beam will be tested of effective span of 3 m subjected to four point loadings. The strain gauge are uses to measures the strain while the deflection were measured using LVDT. All beams in this study are rectangular beams with dimension of 200mm x 150mm for width and height. This result were compare with rectangular solid beam. The results show that the longitudinal opening affected the initial crack and deflection of the beam due to the decreasing of second moment of inertia. Initial crack which observed was appeared at the support . So this beam failed due to shear. The results shows that the increasing size hollow section will increasing the deflection and initial crack of the beam.